ANALYSIS OF THE EFFECT OF ELEVATION DIFFERENCE BETWEEN HEATER AND COOLER POSITION IN THE FASSIP-01 TEST LOOP USING RELAP5 - Andi Sofrany Ekariansyah; Hendro Tjahjono; Mulya Juarsa; Surip Widodo (Badan Tenaga Nuklir Nasional, 2015)
To understand the natural circulation phenomena on the passive residual heat removal system (PRHRS), development of a test section describing that phenomena in particular in the one phase condition is required. That test facility is named as FASSIP-01 in form of a vertically closed loop consisting of piping compo-nents, one cylinder tank featured with heater elements and one cooler. The heater tank will work as the heat source, and the cooler as the heat sink. This research is intended to support the experimental activity of the FASSIP-01 by conducting a simulation using the RELAP5/SCDAP/Mod3.4. Beside the standard loop configuration, the simulation is also conducted by varying the elevation of heater and cooler position to evaluate the best position resulting in the most optimal natural circulation. The results will be used as the comparison with the later performed experiment. The simulation result shows that for the case where the heater position is at the same level with the cooler position, the temperature distribution of the water after the heater and after the cooler are higher than the other two position. Looking at the natural circulation, that position results in the lowest mass flow. The position with the heater below the cooler will result in the best mass flow. On that position, only an optimiza-tion in the heat transfer surface area is needed to increase the heat transfer coefficient and secondary mass flow to remove the heat are needed to obtain more optimal performance of the water circulation caused by the density difference in the FASSIP-01 test loop.